A case report of incidental ectopic pancreatic tissue during laparoscopic appendicectomy. (2018) - So, Hang-Fai; Cross, Trent J.; Zonta, Mark
Highlights: Jejunal ectopic pancreatic tissue is rare. Pre-operative diagnosis is often difficult. Jejunojejunal intussusception can results from ectopic pancreatic tissue. Resection is the management of choice for incidentally found jejunal ectopic pancreatic tissue. Abstract: Introduction: Ectopic or heterotopic pancreas is a congenital disorder defined as abnormally located pancreatic tissue found outside the pancreatic frame. It is a rare entity that occasionally causes symptoms depending on its location. Presentation of case: We present the case of an incidental finding of proximal jejunal ectopic pancreas in a middle-aged woman presenting with appendicitis. Discussion and conclusion: Although rare it is necessary to be aware that jejunal ectopic pancreas can lead to jejunojejunal intussusception. Although diagnostic tools are emerging, pre operative diagnosis is difficult and resection is the management of choice of the incidentally found lesion.